The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/qai.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perinatally Acquired HIV Disease Upon Longitudinal Changes in Memory and Executive Functioning

Abstract: Background Little is known regarding effects of perinatally-acquired HIV infection (PHIV) on longitudinal change in memory and executive functioning (EF) during adolescence, despite the importance of these skills for independence in adulthood. Methods PHIV (n=144) and perinatally HIV-exposed uninfected youth (PHEU, n=79), ages 12–17, completed standardized tests of memory and EF at baseline and two years later. Changes from baseline for each memory and EF outcome were compared between PHEU and PHIV youth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
6
28
1
Order By: Relevance
“…We also observed children who developed acquired motor deficits, failure to attain or loss of psychomotor developmental milestones, neurocognitive delay (non-meeting CDC diagnostic criteria for HIV-1 encephalopathy). This finding reflects what observed in other recent studies: even if the introduction of cART reduced the rates of HIV-1-related encephalopathy (43,44,50), milder neurocognitive deficits (lower total intelligence quotient, language impairment, poorer working memory, gross and fine motor functioning, visual-motor impairment) are diagnosed more and more frequently (51)(52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 89%
“…We also observed children who developed acquired motor deficits, failure to attain or loss of psychomotor developmental milestones, neurocognitive delay (non-meeting CDC diagnostic criteria for HIV-1 encephalopathy). This finding reflects what observed in other recent studies: even if the introduction of cART reduced the rates of HIV-1-related encephalopathy (43,44,50), milder neurocognitive deficits (lower total intelligence quotient, language impairment, poorer working memory, gross and fine motor functioning, visual-motor impairment) are diagnosed more and more frequently (51)(52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast with previous literature, our study did not reveal associations of executive functioning with medical characteristics, which could be explained by the limited sample size or the little variation in current medical characteristics due to successful treatment with cART. Previous studies found associations between lower CD4 cell count, a history of AIDS-defining diagnoses, and higher peak viral load with compromised executive functioning [43,44]. These studies and our finding that HIV-infected children have more teacher-reported problems in their executive functioning than their siblings, support the hypothesis that the HIV-infection is a contributor to cognitive problems, especially executive functioning.…”
Section: Discussionsupporting
confidence: 87%
“…These studies and our finding that HIV-infected children have more teacher-reported problems in their executive functioning than their siblings, support the hypothesis that the HIV-infection is a contributor to cognitive problems, especially executive functioning. The development of problems in executive functioning is of significant concern for its negative impact on academic learning, successful transition to adulthood, and medication adherence [43,45]. Hence, care providers should be aware of the risk for compromised executive functioning in HIV-infected children, and refer them to a neuropsychologist if problems in this domain arise.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 32 ] For example, diminished CT in the orbitofrontal area in adolescence correlates to impulsive behavior, [ 33 ] and an executive function known as inhibition, deficit of which has been widely described in PHIV patients. [ 34 36 ]…”
Section: Discussionmentioning
confidence: 99%